Traditional Japanese design motifs - D'Addetta, Joseph (New York : Dover Publications, 1984)
A treasury of hundreds of authentic Japanese design motifs--all copyright-free and easy to reproduce.
-- Plants and flowers -- Animal life -- Human figures -- Symbolic object -- Geometric patterns -- Water and wave forms -- Ceramic object.
Keywords: Decoration and ornament -- Japan -- Themes, motives